Young-Onset Diabetes in Sri Lanka: Experience From the Developing World - Maulee Hiromi Arambewela; Shani A. D. Mathara Diddhenipothage; Chandrika Jayakanthi Subasinghe; Umesha Nuwanrasee Wijenayake; Surangi Jayakody; Gowri M. Ratnayake; Charles Antonypillai; Sachith Abhayaratne; Chaminda Garusinghe; Prasad Katulanda; Noel Somasundaram; Uditha Bulugahapitiya; et al. (Journal of Diabetes Research)
Conclusion: T1D was the commonest subtype of YOD in this hospital-based population. However, T2D was notably higher and is of significant concern. Overall, suboptimal glycaemic control and high rate of complications were noted along with substandard insulin regimens and BG monitoring.